2017
DOI: 10.1016/j.pmedr.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Full fat milk consumption protects against severe childhood obesity in Latinos

Abstract: Consumption of non- or low-fat dairy products is recommended as a strategy to lower the risk of childhood obesity. However, recent evidence suggests that consumption of whole fat dairy products may, in fact, be protective against obesity. Our objective was to determine the association between milk fat consumption and severe obesity among three-year-old Latino children, a population with a disproportionate burden of obesity and severe obesity. 24-hour-dietary recalls were conducted to determine child intake in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 26 publications
5
27
0
Order By: Relevance
“…Moreover, Beck (2017) has shown that higher milk fat consumption is associated with lower correlation with severe obesity among Latino preschoolers [31]. In addition, a number of cross-sectional studies have reported an inverse correlation between BMI or adiposity and dairy product consumption in children, which is lined with our results.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, Beck (2017) has shown that higher milk fat consumption is associated with lower correlation with severe obesity among Latino preschoolers [31]. In addition, a number of cross-sectional studies have reported an inverse correlation between BMI or adiposity and dairy product consumption in children, which is lined with our results.…”
Section: Discussionsupporting
confidence: 91%
“…It is notable that evidence is accumulating that higher fat, rather than low-fat, dairy is associated with a lower risk of obesity and diabetes, 21 23–25 including several studies that suggest full fat milk is associated with reduced risk of overweight and obesity in children. 25 59 60 …”
Section: Discussionmentioning
confidence: 99%
“…Low fat milk and dairy foods are often recommended as health alternatives to reduce energy density and saturated fat intake 383 . However, our finding that full fat milk was negatively associated with body fat percent joins other cross-sectional and prospective studies and literature reviews that call this recommendation into question 138,270,374,375,378,387 .…”
Section: Resultssupporting
confidence: 79%